Incremental Growth of Layered Mafic-Ultramafic Intrusions Through Melt Replenishment Into a Crystal Mush Zone Traced by Fe-Hf Isotope Systematics - Nebel, Oliver; Sossi, Paolo A.; Ivanic, Timothy J.; Bénard, Antoine; Gardiner, Nicholas J.; Langford, Richard L.; Arculus, Richard J. (Frontiers in Earth Science, 2020)
Layered mafic-ultramafic intrusions are among the largest igneous bodies on Earth, and represent aggregations of large volumes of mantle- and some crustal-derived melts. Melts are emplaced over time-intervals of less than one million years, predominantly through multiple pulses of injections into pre-existing melt-crystal slurries. The dynamic interaction of physical processes, including density-driven separation and mixing of different components, within a solidifying magma chamber leads to such extreme chemical diversity between cumulate rock units, that no unified model currently explains all aspects of the genesis of these intrusions. Here we present whole-rock stable Fe isotope data (expressed in ‰ variations as 57Fe relative to IRMM-014) for samples of drill core taken from the stratified paleo-magma chamber of the Upper Zone of the late-Archean Windimurra Igneous Complex, Western Australia. Variations from near chondritic (57Fe ~ +0 ‰) to heavy (57Fe~ +0.2 ‰) values show a co-variation with initial radiogenic Hf isotope data that is unique to the Windimurra Upper Zone. The systematic isotopic variations from the roof to the base of the Upper Zone are best explained by an intricate sequence of events that included fractional crystallisation and physical mixing. We propose that melt freshly sourced from the mantle was injected into and inflated a pre-existing crystal-melt mush comprising the upper Middle Zone. Re-establishment of crystal layering after replenishment introduced a chemical stratification with the formation of what became the Upper Zone and a crystal-interstitial melt ratio decreasing from roof to base. Basal, vanadiferous magnetitite horizons crystallised through enhanced fO2 during liquid replenishment. Variable degrees of perturbation and chaotic stirring of crystals with imperfect mixing of new and old components was followed by rapid crystal settling and subsequent cumulate stratification. Such melt rejuvenation, proposed here to be the cause for a newly established Upper Zone, leaves no unique petrologic fingerprint but can explain not only the observed coupled Fe-Hf isotope systematics but also mineral disequilibria and cryptic layering in layered intrusions.